Endometrial cancer: guideline of the DGGG, DKG and DKH (S3-Level, AWMF Registry Number 032/034-OL, September 2022) : part 1 with recommendations on the epidemiology, screening, diagnosis and hereditary factors of endometrial cancer, geriatric assessment and supply structures = Endometriumkarzinom : Leitlinie der DGGG, DKG und DKH (S3-Level, AWMF-Register-Nummer 032/034-OL, September 2022) : Teil 1 mit Empfehlungen zu Epidemiologie, Früherkennung, Diagnostik, hereditären Faktoren des Endometriumkarzinoms, geriatrischem Assessment und Versorgungsstrukturen - Emons, Günter; Steiner, Eric; Vordermark, Dirk; Uleer, Christoph; Paradies, Kerstin; Tempfer, Clemens; Aretz, Stefan; Cremer, Wolfgang; Hanf, Volker; Mallmann, Peter; Ortmann, Olaf; Römer, Thomas; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Summary: The S3-guideline on endometrial cancer, first published in April 2018, was reviewed in its entirety between April 2020 and January 2022 and updated. The review was carried out at the request of German Cancer Aid as part of the Oncology Guidelines Program and the lead coordinators were the German Society for Gynecology and Obstetrics (DGGG), the Gynecology Oncology Working Group (AGO) of the German Cancer Society (DKG) and the German Cancer Aid (DKH). The guideline update was based on a systematic search and assessment of the literature published between 2016 and 2020. All statements, recommendations and background texts were reviewed and either confirmed or amended. New statements and recommendations were included where necessary. Aim: The use of evidence-based risk-adapted therapies to treat women with endometrial cancer of low risk prevents unnecessarily radical surgery and avoids non-beneficial adjuvant radiation therapy and/or chemotherapy. For women with endometrial cancer and a high risk of recurrence, the guideline defines the optimum level of radical surgery and indicates whether chemotherapy and/or adjuvant radiation therapy is necessary. This should improve the survival rates and quality of life of these patients. The S3-guideline on endometrial cancer and the quality indicators based on the guideline aim to provide the basis for the work of certified gynecological cancer centers. Methods: The guideline was first compiled in 2018 in accordance with the requirements for S3-level guidelines and was updated in 2022. The update included an adaptation of the source guidelines identified using the German Instrument for Methodological Guideline Appraisal (DELBI). The update also used evidence reviews which were created based on selected literature obtained from systematic searches in selected literature databases using the PICO process. The Clinical Guidelines Service Group was tasked with carrying out a systematic search and assessment of the literature. Their results were used by interdisciplinary working groups as a basis for developing suggestions for recommendations and statements which were then modified during structured online consensus conferences and/or additionally amended online using the DELPHI process to achieve a consensus. Recommendations: Part 1 of this short version of the guideline provides recommendations on epidemiology, screening, diagnosis, and hereditary factors. The epidemiology of endometrial cancer and the risk factors for developing endometrial cancer are presented. The options for screening and the methods used to diagnose endometrial cancer are outlined. Recommendations are given for the prevention, diagnosis, and therapy of hereditary forms of endometrial cancer. The use of geriatric assessment is considered and existing structures of care are presented.
Artikel online veröffentlicht: 15. August 2023